Tiroidektomi Endoskopi Transoral dengan Pendekatan Vestibular Untuk Nodul Tiroid: Serial 12 Pasien Pertama di RSUP Prof. Dr. R. D. Kandou - Riston R. Sitompul; Victor Pontoh; Marselus Merung; Christian Manginstar (Medical Scope Journal, 2024)
Abstract: Transoral endoscopic thyroidectomy by vestibular approach (TOETVA), showed a comparable result to the conventional thyroidectomy, without any scar as the advantage. This study aimed to present the feasibility and safety of patients with solitary or multinodular goitre and or papillary thyroid carcinoma using TOETVA. This was a case series using 12 patients recorded undergoing TOETVA procedure. Eleven patients’ specimen obtained through FNAB resulted as benign nodule. In one patient, the nodule was malignant and unilateral, therefore, endoscopic isthmolobectomy was performed. Outcomes and measures included conversion to open conventional surgery, operative time, intraoperative blood loss, size of the thyroid gland, postoperative hospital stay, visual analogue scores, and postoperative complications. The results showed a total of 12 patients; all were women, aged 33-64 years. The size of thyroid nodules ranged from 2 cm to 7 cm. One patient got converted to open isthmus lobectomy. In this series, none of the patients were noted to have mental nerve injury but two patients developed anterior neck chin skin bruise. The mean postoperative VAS measurements were 2, 1, and no pain or 0, on the first, second, third, and seventh postoperative days, respectively. In conclusion, endoscopic thyroidectomy is feasible, safe, and comparable to open thyroidectomy and yields excellent aesthetic results. Keywords: endoscopic thyroidectomy; minimally invasive surgical procedures; thyroid neoplasms    Abstrak: Tiroidektomi endoskopi transoral dengan pendekatan vestibular (TOETVA), menunjuk-kan hasil sebanding dengan tiroidektomi konvensional, tanpa adanya bekas luka sebagai keuntungan. Penelitian ini bertujuan untuk menyajikan kelayakan dan keamanan pasien dengan penyakit gondok soliter atau multinodular dan atau karsinoma tiroid papiler menggunakan TOETVA. Jenis penelitian ialah serial kasus yang menjalani TOETVA selama Januari 2018 hingga Desember 2019 di RSUP Prof. Dr. R. D. Kandou. Terdapat 12 pasien tercatat menjalani prosedur TOETVA; 11 spesimen pasien diambil melalui FNAB dan menghasilkan nodul jinak. Pada salah satu pasien didapatkan nodul ganas unilateral sehingga dilakukan istmolobektomi endoskopi. Hasil dan tindakan termasuk konversi ke operasi konvensional terbuka, waktu operasi, kehilangan darah intraoperatif, ukuran kelenjar tiroid, rawat inap pasca operasi, VAS, dan komplikasi pasca operasi. Hasil penelitian mendapatkan 12 pasien, semuanya berjenis kelamin perempuan, berusia 33-64 tahun. Ukuran nodul tiroid berkisar 2 - 7 cm. Satu pasien diubah menjadi lobektomi terbuka. Tidak ada pasien yang tercatat mengalami cedera saraf mental, namun dua pasien mengalami memar pada kulit dagu leher bagian depan. Rerata pengukuran VAS pasca operasi ialah 2, 1, dan tidak nyeri atau 0, masing-masing pada hari pertama, kedua, ketiga, dan ketujuh pasca operasi. Simpulan penelitian ini ialah tiroidektomi endoskopi layak dilakukan, aman dan sebanding dengan tiroidektomi terbuka serta memberikan hasil estetika yang sangat baik. Kata kunci: tiroidektomi endoskopi transoral; minimal invasif; neoplasma tiroid